Program dan Kegiatan Humas Sekretariat Daerah Aceh Dalam Menjalankan Hubungan Media - Eva Hazmaini (Ar-Raniry State Islamic University, Indonesia, 2019)
The article discusses the PR programs and activities of the Humas Sekretariat Daerah Aceh in carrying out relations with the media that are related to one another. PR programs and activities undertaken to build a positive image of government. This paper says that the cooperation between the Humas Sekretariat Daerah Aceh with the media has been very well established, but there are still some shortcomings and obstacles that exist in the PR and the media itself.